New Perianal Sepsis Risk Score Predicts Outcome of Elderly Patients with Perianal Abscesses - Reichert, Martin; Eckerth, Lukas; Fritzenwanker, Moritz; Imirzalioglu, Can; Amati, Anca-Laura; Askevold, Ingolf; Padberg, Winfried; Hecker, Andreas; Liese, Juliane; Bender, Fabienne; Justus Liebig University Giessen (My University, 2023)
Antibiotic therapy following surgical perianal abscess drainage is debated, but may be necessary for high-risk patients. Frailty has been shown to increase the risk of unfavorable outcomes in elderly surgical patients. This study aims to identify high-risk patients by retrospectively analyzing a single-center cohort and using a pretherapeutic score to predict the need for postoperative antibiotics and extended nursing care following perianal abscess drainage surgery. The perianal sepsis risk score was developed through univariable and multivariable analysis. Internal validation was assessed using the area under receiver-operating characteristic curve. Elderly, especially frail patients exhibited more severe perianal disease, higher frequency of antibiotic therapy, longer hospitalization, poorer clinical outcomes. Multivariable analysis revealed that scores in the 5-item modified frailty index, severity of local infection, and preoperative laboratory markers of infection independently predicted the need for prolonged hospitalization and anti-infective therapy after abscess drainage surgery. These factors were combined into the perianal sepsis risk score, which demonstrated better predictive accuracy for prolonged hospitalization and antibiotic therapy compared with chronological age or frailty status alone. Geriatric assessments are becoming increasingly important in clinical practice. The perianal sepsis risk score identifies high-risk patients before surgery, enabling early initiation of antibiotic therapy and allocation of additional nursing resources.
Keywords: ddc:610